PSYCHOLOGICAL ASPECTS OF HOLDING OF THE MASS EVENTS ON THE MODERN SPORT BUILDINGS - Lefterov, V.; Servachak, O.; Alexentseva-Timchenko, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article is devoted to the psychological aspects of holding mass sport events on the modern sport stadiums. On the basis of analyzing of the modern practice of organization and holding European and World football championships the psychological peculiarities of holding mass sport events on the modern mega stadiums are found. The article outlines the results of the empiric research of the psychological peculiarities of a person and the activity of stadium staff. The necessity of the psychological support system for organization and holding mass sport events is proved.